Adiponectin as Well as Compressive Forces Regulate in vitro β-Catenin Expression on Cementoblasts via Mitogen-Activated Protein Kinase Signaling Activation - Yong, Jiawen; von Bremen, Julia; Ruiz-Heiland, Gisela; Ruf, Sabine (Frontiers in Cell and Developmental Biology, 2021)
We aimed to investigate the molecular effect that adiponectin exerts on cementoblasts especially in the presence of compressive forces. OCCM-30 cells (M. Somerman, NIH, NIDCR, USA) were used. RT-PCR and western blots were employed to verify the mRNA and protein levels of adiponectin receptors (AdipoRs), MAPK and β-Catenin signaling influenced by compressive forces or adiponectin. Moreover, siRNAs targeting P38α, JNK1, ERK1, ERK2 and AdipoRs as well as pharmacological MAPK inhibition were performed. We found that compressive forces increase expression of AdipoRs. Adiponectin and compression up-regulate P38α，JNK1, ERK1 and ERK2 as well as β-Catenin gene expression. Western blots showed that co-stimuli activate MAPK and β-Catenin signaling pathway. The MAPK inhibition alters the compression-induced β-Catenin activation and the siRNAs targeting AdipoRs, P38α and JNK1, showing the interaction of single MAPK molecules and β-Catenin signaling in response to compression or adiponectin. Silencing by dominant negative-version of P38α and JNK1 attenuate adiponectin-induced TCF/LEF reporter activation. Together, we found that light compressive forces activate β-Catenin and MAPK signaling pathways. Adiponectin regulates β-Catenin signaling principally by inactivating GSK-3β kinase activity. β-Catenin expression was partially inhibited by MAPK blockade indicating that MAPK plays a crucial role regulating β-Catenin during cementogenesis. Moreover, adiponectin modulates GSK-3β and β-Catenin mostly through AdipoR1. P38α is a key connector between β-Catenin, TCF/LEF transcription and MAPK signaling pathway.